Method for directly repairing waste lithium ion battery positive electrode material through multifunctional lithium salt

By using multifunctional lithium salts to repair cathode materials of waste lithium iron phosphate and lithium manganese iron phosphate batteries, the problems of high energy consumption and high pollution in existing technologies have been solved, achieving performance restoration and cost reduction. It is applicable to the repair of various waste batteries.

CN120987289APending Publication Date: 2025-11-21HUAQIAO UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511105935.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively restore the electrochemical performance of spent lithium iron phosphate and lithium manganese iron phosphate batteries, and traditional remediation methods suffer from high energy consumption, pollution, and high costs.

Method used

A multifunctional lithium salt is used to directly repair the cathode materials of waste lithium iron phosphate and lithium manganese iron phosphate batteries. Through ball milling and high-temperature sintering, lithium is replenished, iron is reduced, lithium iron antisites and nitrogen doping are reduced, and the material properties are restored.

Benefits of technology

It significantly improves the cycle stability and rate performance of spent lithium iron phosphate and lithium manganese iron phosphate batteries, reduces recycling costs, and has a simple and environmentally friendly process, making it suitable for the repair of various spent battery cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987289A_ABST
    Figure CN120987289A_ABST
Patent Text Reader

Abstract

The invention discloses a method for directly repairing a positive electrode material of a waste lithium ion battery through multifunctional lithium salt. The method comprises the following steps: (1) collecting waste lithium iron phosphate or lithium iron manganese phosphate batteries, stripping positive plates after disassembling, and ultrasonically cleaning to remove a binder, so as to obtain a waste positive electrode material with uniform components; (2) detecting and determining the content of each element in the waste positive electrode material through ICP-MS; (3) adding the waste positive electrode material and the multifunctional lithium salt into a ball milling tank, and performing ball milling to reduce the particle size and promote full mixing of the lithium salt and the waste positive electrode material; and (4) heating and sintering the mixed material under the protection of argon, and then naturally cooling. According to the invention, the multifunctional lithium salt is utilized to carry out lithium supplement repair on the electrode, so that multiple effects of lithium supplement, iron reduction, reduction of lithium-iron antiposition, nitrogen doping and the like can be realized in one step. And the method has the advantages of simplicity in operation, low cost, good repairing effect and capability of repairing various positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lithium ion battery cathode material recycling, and particularly relates to a method for repairing waste lithium ion battery cathode material by using a multifunctional lithium salt. BACKGROUND

[0002] In recent years, the explosive growth of new energy vehicles has led to an increasing amount of discarded lithium ion batteries, and the proper disposal of waste batteries has become an important problem to be solved.

[0003] The current lithium ion battery recycling method mainly includes fire and wet recovery. The fire recovery recovers the metal elements in the battery in the form of an alloy through high-temperature calcination. Although this method has a relatively simple process and a shorter flow, the high-temperature calcination process has a huge energy consumption and easily produces a large amount of waste gas and waste residue, causing serious environmental pollution. The wet recovery selectively leaches the metals in the cathode material by means of acid, alkali or microorganisms, and then prepares valuable metal compounds or elements through extraction separation or coprecipitation. This method has a relatively low energy consumption and a high metal extraction rate, but a large amount of leaching wastewater is generated during the recovery process, which can easily cause secondary pollution if not properly treated. For lithium iron phosphate and lithium manganese iron phosphate cathode materials, they do not contain high-valence metals such as cobalt and nickel, and the economic efficiency of traditional fire or wet recovery is poor.

[0004] The main reason for the capacity attenuation of lithium iron phosphate and lithium manganese iron phosphate batteries after long-term cycling is the loss of lithium. After the loss of lithium, vacancies are left, so part of Fe will migrate to the position of lithium to form Li-Fe anti-site defects, thereby occupying active sites and blocking lithium ion transport channels. The loss of lithium will also induce Fe 2+ to Fe 3+ , forming FePO4 phase and affecting battery performance. Therefore, to restore the composition and structure of the failed cathode material to the original state, it is necessary to supplement the lost lithium, reduce Fe 3+ , and reduce lithium-iron anti-site, etc. Therefore, achieving the optimal sustainable recycling of waste lithium ion batteries has become the direction of researchers' efforts.

[0005] The traditional inorganic lithium salt (such as lithium carbonate, lithium hydroxide, etc.) solid-phase sintering regeneration method can only solve the single problem of lithium loss and cannot simultaneously achieve the effects of iron valence reduction and reduction of lithium-iron anti-site, resulting in limited repair effect. The repair strategy using a lithium source and a reducing agent requires the consumption of more materials, increasing the repair cost, and the lithium salt and the reducing agent will also have a negative effect. Therefore, developing a safe, environmentally friendly and cost-competitive repair method is crucial for the repair of lithium iron phosphate and lithium manganese iron phosphate.

[0006] In this context, the present patent proposes a method for directly repairing waste lithium iron phosphate with multifunctional lithium salt. This method can achieve four functions, including supplementing the missing lithium in the material, reducing trivalent iron, reducing lithium-iron inversion, and nitrogen doping, in one step. It has obvious advantages and can solve many problems in the prior art, achieving efficient and environmentally friendly recycling and reuse of waste lithium iron phosphate and manganese iron phosphate batteries. SUMMARY

[0007] The present application aims to provide a method for directly repairing waste lithium iron phosphate and manganese iron phosphate with multifunctional lithium salt. This method can effectively restore the electrochemical performance of waste lithium iron phosphate and manganese iron phosphate, solve the problem of high-value recycling, and has a simple process and is environmentally friendly.

[0008] The technical solution of the present application is as follows: A method for repairing waste lithium ion battery anode material with multifunctional lithium salt, comprising the following steps: (1) Collecting waste lithium iron phosphate and manganese iron phosphate batteries with a capacity loss rate of 80%, disassembling to obtain lithium iron phosphate and manganese iron phosphate materials. Clean the lithium iron phosphate or manganese iron phosphate anode material to remove the binder, and then dry to obtain a uniform composition material.

[0009] (2) Detecting the elements of the obtained material to determine the amount of lithium loss. Add prepared multifunctional lithium salts such as LiNH2, Li3N, LiC2H5, LiH, etc. to the waste material according to 1.0-2.0 times the amount of lithium loss substance. These lithium salts have a special structure and have the functions of reduction, reducing lithium-iron inversion, etc. in addition to lithium supplementation. LiNH2 and Li3N also have the function of nitrogen doping, which can repair the electrode material while improving its conductivity.

[0010] (3) Add the mixed material to a ball mill jar and perform ball milling to fully mix the raw materials and form a uniform mixture, while reducing the particle size of the material and increasing the contact between the multifunctional lithium salt and the waste lithium iron phosphate particles or waste manganese iron phosphate particles. The ball milling ratio of the ball milling beads to the material is 10:1, the ball milling frequency is 25 Hz, and the ball milling time is 5-120 min.

[0011] (4) The mixed material is transferred into a crucible and placed into a high-temperature tube furnace for heat treatment under the protection of argon. The sintering temperature is 300-900 DEG C, and the sintering time is 0.5-12 h. During the high-temperature sintering process, lithium ions in the multifunctional lithium salt are embedded into the crystal lattice to realize lithium supplement for the waste lithium iron phosphate or waste lithium manganese iron phosphate. In addition, the anions in the lithium salt or their decomposition products have reducing properties, which can reduce the trivalent iron to divalent iron and promote the divalent iron to return to the original position to reduce lithium-iron transposition. In addition, part of the lithium salt also has the effect of nitrogen doping to improve the electronic conductivity of the material.

[0012] (5) After the heat treatment, the repaired lithium iron phosphate and lithium manganese iron phosphate material is obtained by naturally cooling to room temperature under the protection of inert gas.

[0013] In a preferred embodiment of the present application, the lithium content in the system is determined by ICP-MS detection in step (2), and the lithium loss amount is calculated by comparison with the standard lithium iron phosphate. The selected multifunctional lithium salt is one of LiNH2, Li3N, LiC2H5, LiH and the like.

[0014] In a preferred embodiment of the present application, the ball milling time in step (3) is 5-120 min.

[0015] In a preferred embodiment of the present application, the sintering temperature in step (4) is 300-900 DEG C, and the sintering time is 0.5-12 h.

[0016] The present application has the following advantages: 1. The performance is significantly improved. The repaired lithium iron phosphate positive material has excellent cycle stability and rate performance, and the repair effect is better than that of the conventional repair material (i.e. lithium salt + reducing agent repair). This is due to the effects of effective lithium supplement, reduction of trivalent iron, reduction of lithium-iron transposition and nitrogen doping.

[0017] 2. The process is simple and environmentally friendly. The present application does not require complex equipment and multi-step reactions, and the repair of waste lithium iron phosphate can be realized by mechanical ball milling and simple heat treatment. The whole process does not use strong acid and strong base, produces less waste gas and waste residue, is friendly to the environment, and meets the requirements of sustainable development.

[0018] 3. Low cost. The multifunctional lithium salt is widely available and relatively low in price, and the present application has high raw material utilization rate, does not require expensive equipment and complex operation. Compared with the current strategy of using lithium salt and reducing agent, the present application uses less consumables, achieves multiple functions, greatly reduces the recycling cost, and has high economic benefits.

[0019] 4. Strong versatility. The method is not only suitable for repairing waste and old lithium iron phosphate and lithium manganese iron phosphate positive electrode materials, but also can be applied to the repair of other transition metal oxide layered positive electrode materials after proper adjustment, providing a new way for the recycling of various waste battery positive electrode materials. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 XRD patterns of Example 1 and Comparative Examples 1, 3.

[0021] Figure 2 FTIR patterns of Example 1 and Comparative Examples 1, 3.

[0022] Table 1 is the elemental analysis test results of Example 1 and Comparative Example 1.

[0023] Figure 3 Cycle performance of Example 1 and Comparative Examples 1, 3 at 0.2C current density.

[0024] Figure 4 XRD patterns of Example 2 and Comparative Example 2.

[0025] Figure 5 Cycle performance of Example 2 and Comparative Example 2 at 0.2C current density.

[0026] Figure 6 Cycle performance of Example 1 and Comparative Examples 1, 4-6 at 0.2C current density.

[0027] Figure 7 Cycle performance of Example 1 and Comparative Examples 1, 7-8 at 0.2C current density.

[0028] Figure 8 Cycle performance of Example 1 and Comparative Examples 1, 9-10 at 0.2C current density.

[0029] Figure 9 Cycle performance of Example 1 and Comparative Examples 1, 11-12 at 0.2C current density.

[0030] Figure 10 Cycle performance of Example 1 and Comparative Examples 1, 13-14 at 0.2C current density. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present application more clear, the technical scheme of the embodiments of the present application will be described clearly and completely.

[0032] The specific conditions are not indicated in the examples, and the conventional conditions are used; the reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be purchased on the market. It needs to be stated that the lithium ion batteries repaired by the present application are all based on lithium iron phosphate batteries or lithium manganese iron phosphate batteries, and all within the technical features related to the present application are within the scope of the present application.

[0033] The repair method of the failed electrode provided by the present application is described in detail below.

[0034] The loss of active lithium, the oxidation of iron and the generation of lithium-iron inversion are the three main reasons for the capacity decline of the positive electrode material during the charging and discharging process. In the failed lithium ion positive electrode sheet, the positive electrode material is in different states under different conditions. It can be referred to that the waste lithium iron phosphate battery with a capacity decline of 80% still maintains a good olivine crystal structure, which provides the possibility for direct repair.

[0035] Based on this, the present application provides a method for directly repairing waste lithium ion battery positive electrode material by using multifunctional lithium salt, which comprises the following steps: (1) The waste lithium ion battery with a battery capacity loss rate of more than 80% is discharged, and then disassembled and collected to obtain the positive electrode material. The binder is removed by cleaning, and then dried to store lithium. Then the lithium content in the obtained positive electrode sheet is determined by ICP method, and then compared with the lithium content in the positive electrode material of the same type of new lithium ion battery, and the loss of lithium is calculated; (2) The multifunctional lithium salt and the collected waste positive electrode material are mixed by ball milling, the amount of multifunctional lithium salt is 1-2 times the amount of substance of lithium loss, zirconia ball milling beads are used in the ball milling process, the mass ratio of beads is 10:1, the ball milling frequency is 25Hz, and the ball milling time is 5-120min.

[0036] (3) After ball milling, the material is subjected to high temperature sintering treatment under argon protection, the sintering temperature is 300-900℃, and the sintering time is 0.5-12h. The repaired material is obtained after sintering.

[0037] The following specific embodiments further illustrate and describe the technical solutions of the present application in conjunction with the drawings.

[0038] Example 1 (1) The waste lithium iron phosphate battery with a battery capacity loss rate of 80% is discharged to 2.5V at a current density of 0.1C, disassembled, and the positive electrode sheet is peeled off. It is placed in N-methyl pyrrolidone (NMP), and the binder PVDF is removed by ultrasonic cleaning for 30min at 30kHz. The obtained positive electrode material is washed with anhydrous ethanol for three times, and finally dried at 80℃ for 6h to obtain the waste lithium iron phosphate positive electrode material.

[0039] (2) The lithium element loss amount of the material is determined by ICP-MS detection, and the multifunctional lithium salt LiNH2 is added at 1.2 times the amount of the lithium loss substance, and mixed uniformly.

[0040] (3) The uniformly mixed powder is transferred into a polytetrafluoroethylene ball mill tank (the mass ratio of the beads to the powder is 10:1), and ball milled at a frequency of 25 Hz for 30 min to form a uniform black powder.

[0041] (4) The black powder is transferred to a crucible and placed in a high-temperature tube furnace, argon gas is introduced as a protective gas, the temperature is raised to 750°C at a rate of 5°C / min, and after holding for 3 h, it is naturally cooled to room temperature to obtain the repaired cathode material.

[0042] Example 2 The waste lithium iron phosphate battery in step (1) of Example 1 is replaced with a waste lithium manganese iron phosphate battery, and the rest is the same as Example 1.

[0043] Comparative Example 1 The waste lithium iron phosphate battery with a battery capacity loss rate of 80% is discharged to 2.5V at a current density of 0.1C, and after disassembly, the positive plate is peeled off, placed in NMP, and cleaned with 30kHz ultrasonic for 30min to remove the binder PVDF. The obtained positive material is washed with anhydrous ethanol three times, and finally dried at 80°C for 6h to obtain the waste lithium iron phosphate positive material.

[0044] Comparative Example 2 The waste lithium iron phosphate battery in Comparative Example 1 is replaced with a waste lithium manganese iron phosphate battery, and the rest is the same as Comparative Example 1.

[0045] Comparative Example 3 Repairing lithium iron phosphate material by conventional repair method LiNH2 in step (2) of Example 1 is replaced with LiOH, and the same amount of urea as LiOH is added, and the rest is the same as Example 1.

[0046] Comparative Examples 4-6 LiNH2 in step (2) of Example 1 is replaced with Li3N, LiC2H5, and LiH, respectively, and the rest is the same as Example 1.

[0047] Comparative Examples 7-8 The amount of LiNH2 in step (2) of Example 1 is changed to 1 times and 2 times, respectively, and the rest is the same as Example 1.

[0048] Comparative Examples 9-10 The ball milling time in step (3) of Example 1 is changed to 5min and 120min, respectively, and the rest is the same as Example 1.

[0049] Comparative Examples 11-12 The sintering temperature in step (4) of Example 1 was changed to 300°C and 900°C, respectively, and the rest was the same as Example 1.

[0050] Comparative Examples 13-14 The sintering time in step (4) of Example 1 was changed to 0.5h and 12h, respectively, and the rest was the same as Example 1.

[0051] The positive electrode material prepared in the above examples and comparative examples was applied to a battery, as follows: The repaired lithium iron phosphate or lithium manganese iron phosphate positive electrode powder was mixed with acetylene black and a binder in a mass ratio of 8:1:1 to prepare a positive electrode slurry, which was then coated on an aluminum foil. After drying in a vacuum oven at 80°C overnight, the positive electrode was cut into a 12 mm diameter electrode piece with a loading mass of 3-4 mg cm -2 A CR2032 button cell was assembled in an argon-filled glove box, with a metal lithium negative electrode and an electrolyte of 1 mol / L LiPF6 solution (solvent: EC-DMC-DEC in a volume ratio of 1:1:1). The button cell was tested for charge-discharge cycling performance using a LAND CT2001 battery test system, with a test temperature of 25±2°C, a voltage window of 2.5-4.2V, and a charge-discharge rate of 0.2C (1C=170mA / g).

[0052] The experimental results of the above examples and comparative examples are as follows: Figure 1 The XRD detection results of the lithium iron phosphate material added with the multifunctional lithium salt repaired in Example 1, the waste lithium iron phosphate material in Comparative Example 1, and the lithium iron phosphate material repaired by the conventional method in Comparative Example 3. As can be seen from the comparison, FePO4 exists in the waste lithium iron phosphate material, indicating that lithium is lost. After the repair treatment by the method of the present application and the conventional method, the characteristic peak of FePO4 is basically disappeared, which indicates that the lithium element in the lithium iron phosphate electrode piece is supplemented, and FePO4 is converted to LiFePO4.

[0053] Figure 2 The Fourier infrared spectroscopy results of the lithium iron phosphate material added with the multifunctional lithium salt repaired in Example 1, the waste lithium iron phosphate material in Comparative Example 1, and the lithium iron phosphate material repaired by the conventional method in Comparative Example 3. Since the absorption peaks near 1050 and 1000 cm -1 are related to the P-O stretching vibration of PO4 tetrahedron, and the absorption peak moves to a lower wave number, indicating that the Li-Fe antisite defect concentration around the PO4 tetrahedron is reduced.

[0054] Table 1: Elemental analysis test results of Example 1 and Comparative Example 1 Table 1 is the elemental analysis data of the lithium iron phosphate material added with multifunctional lithium salt repair of Example 1 and the waste lithium iron phosphate material of Comparative Example 1. The carbon, oxygen and nitrogen are measured by an elemental analyzer, and the lithium and iron are measured by ICP-MS. The carbon elements in Example 1 and Comparative Example 1 come from the residual carbon material in the waste battery. According to the results, nitrogen doping is successfully realized in the lithium iron phosphate battery repaired by the multifunctional lithium salt, and the mass percentage content is about 0.7wt%.

[0055] Figure 3 The cycle performance comparison chart of the lithium iron phosphate material added with multifunctional lithium salt repair of Example 1, the waste lithium iron phosphate material of Comparative Example 1 and the lithium iron phosphate material repaired by a conventional method of Comparative Example 3 at a current density of 0.2C. As shown in the chart, at a current density of 0.2C, the capacity of the repaired lithium iron phosphate battery can be increased from 118mAh / g to about 150mAh / g, which is better than that of the lithium iron phosphate repaired by a conventional method (140mAh / g), which proves that the repair treatment can achieve good results.

[0056] Figure 4 The XRD detection results of the lithium manganese iron phosphate material added with multifunctional lithium salt repair of Example 2 and the waste lithium manganese iron phosphate material of Comparative Example 2. As can be seen from the comparison, there are impurity peaks in the waste lithium manganese iron phosphate material, and after the repair treatment by the method of the application, the impurity peaks basically disappear, and the characteristic peaks basically match the standard card.

[0057] Figure 5 The cycle performance comparison chart of the lithium manganese iron phosphate material added with multifunctional lithium salt repair of Example 2 and the waste lithium manganese iron phosphate material of Comparative Example 2 at a current density of 0.2C. As shown in the chart, at a current density of 0.2C, the capacity of the repaired lithium manganese iron phosphate battery can be increased from 120mAh / g to about 147mAh / g, which proves that the repair treatment can also achieve good results in lithium manganese iron phosphate.

[0058] Figure 6 The cycle performance comparison chart of Example 1, Comparative Example 1 and Comparative Examples 4-6 at a current density of 0.2C. As shown in the chart, at a current density of 0.2C, the lithium iron phosphate repaired by different lithium salts all show higher capacity than the waste lithium iron phosphate, which shows that these lithium salts have certain repair effect. The best repair effect is LiNH2, followed by Li3N, LiC2H5 and LiH.

[0059] Figure 7The figure is the cycle performance comparison of Example 1, Comparative Example 7 and Comparative Example 8 at 0.2C current density. As can be seen from the figure, the amount of multifunctional lithium salt has certain influence on the repair of lithium iron phosphate. When 1.2 times of lithium salt is used, the repair effect is best, when 1 times of lithium salt is used, the repair effect is second, and when 2 times of lithium salt is used, the repair effect is worst. Therefore, it can be shown that the amount of lithium salt is not better the more or the less, and it needs a proper amount.

[0060] Figure 8 The figure is the cycle performance comparison of Example 1, Comparative Example 9 and Comparative Example 10 at 0.2C current density. As can be seen from the figure, the ball milling time also has influence on the repair effect. The effect of ball milling for 30 min is best, the effect of ball milling for 5 min is relatively poor due to uneven mixing, and the effect of ball milling for 120 min is worst, which should be that the ball milling time is too long and the structure of the material is damaged.

[0061] Figure 9 The figure is the cycle performance comparison of Example 1, Comparative Example 11 and Comparative Example 12 at 0.2C current density. As can be seen from the figure, the sintering temperature also has certain influence on the repair effect. The sintering effect at 750℃ is best, and the sintering effect at 300℃ and 900℃ is worse than that at 750℃, but the influence effect is not significant, and the samples sintered at 300℃ and 900℃ also show good repair effect.

[0062] Figure 10 The figure is the cycle performance comparison of Example 1, Comparative Example 13 and Comparative Example 14 at 0.2C current density. As can be seen from the figure, the sintering time also has certain influence on the repair effect. The sintering effect for 3h is best, and the sintering effect for 0.5h and 12h is worse than that for 3h, but the difference between them is not large, and both of them also show good repair effect.

[0063] The above is only the preferred embodiment of the present application, and therefore cannot limit the scope of the present application, that is, equivalent changes and modifications made according to the scope of the present patent and the content of the specification should still be within the scope of the present application.

Claims

1. A method for directly repairing cathode materials of spent lithium-ion batteries using multifunctional lithium salts, characterized in that, Includes the following steps: (1) Disassemble the fully discharged waste battery, separate the positive electrode material and dissolve it with N-methylpyrrolidone, and ultrasonically clean it to remove the binder; (2) Determine the amount of lithium loss by elemental analysis, and add multifunctional lithium salt at 1-2 times the amount of lithium loss. (3) Add the waste cathode material and multifunctional lithium salt into the ball mill jar, use zirconia ball milling beads, with a bead-to-material mass ratio of 10:1, a ball milling frequency of 25Hz, and a ball milling time of 5-120 min, and form a uniform mixed system by ball milling. (4) Under argon protection, the mixed material is sintered at 300-900℃ for 0.5-12 hours and then naturally cooled to obtain the repaired cathode material.

2. The method as described in claim 1, characterized in that: In step (1), the waste batteries are selected from either lithium iron phosphate batteries or lithium manganese iron phosphate batteries.

3. The method as described in claim 1, characterized in that: In step (2), the multifunctional lithium salt is selected from at least one of LiNH2, Li3N, LiC2H5, and LiH.

4. The method as described in claim 1, characterized in that: In step (2), the amount of multifunctional lithium salt added is 1-2 times the amount of lithium loss material.

5. The method as described in claim 1, characterized in that: In step (3), the ball milling time is 5-120 min.

6. The method as described in claim 1, characterized in that: In step (4), the sintering temperature is 300-900℃ and the sintering time is 0.5-12 hours.

7. The application of the cathode material repaired by any one of claims 1 to 6 in lithium-ion batteries.